نسق الهوّية و التمثّلات الثقافية في رواية دمية النار لبشير مفتي- أنموذجا – - هلالات, دلال; بالي, محجوبي عقيلة (جامعة الوادي - University of Eloued, 2020)
عرفت الرواية الجزائرية المكتوبة باللغة العربية في السنوات الأخيرة، تحوّلات على مستوى الرؤية والخطاب، حمّلها البحث عن حداثة سّردية مغايرة ،تنفتح بها على الممكن واللاممكن في خطاباتها السّردية، وتعتبر رواية "دمية النار" للروائي بشير مفتي من الروايات التي تبحث في سؤال الهوّية والانتماء،المتمظهرة عبر برامج سّردية مختلفة، والمشكّلة لمجموع من الأنساق الثقافية القابعة تحت أطمار البنى الجمالية لخطابها السّردي،ممّا يتيح للروائي تجسيد ممارسة نصيّة تحقّق التواصل الخارجي المنفتح على اللانهائي،بخلقها شخصيات حيّة تحاكي الواقع وتكسر مجازيتها. تحاول هذه الدّراسة،الكشف عن المرجعيات الثقافيّة المتعدّدة والمشّكلة للخطاب الروائي وما تستثمره هذه المرجعيات من تمثلات وأحداث وشخصيات وخلفيات زمانية وفضائية،ليصبح النصّ الروائي حادثة ثقافيّة ذا أنساق تفاعليّة، ينفتح على تعدّد القراءات التي تؤول إلى اختلاق تأويلات تجعل منه علامة ثقافيّة دالّة. The Algerian novel, written in Arabic in recent years, has known shifts in the level of vision and speech, which have brought it to search for a different narrative modernity, opening it to the possible and the impossible in its narrative speeches, and the novel "Toy of Fire" ("Domiat al-Nar" by the novelist Bashir Mufti is one of the novels that discuss the question of identity and statehood, demonstrated through various narrative programs, forming a group of cultural patterns lurking under the aesthetic structures of its narrative speech, which allows the novelist to embody a textual practice that achieves external communication open to the infinite, by creating living personages that simulate reality and break its metaphor. The aim of this study is to detect the multiple cultural references which form the narrative speech and what this reference invest of representations, events and personages and backgrounds temporal & space, to become a cultural narrative text incident with interactive formats, open to the multiplicity of readings that devolve to fabricate interpretations make him a sign of cultural significance.
مقال
Keywords: الهوّية، الخطاب السّردي،السّردية الثقافيّة،النسق الثقافي،الشّخصية